The Additional Pedestrian’s Behavior: Crossing the Road in Front of an Automated Vehicle in a Wizard of Oz Setting - Maximilian Hubner; Simon Bauer; Florian Bogner; Johanna Dechent; Christoph Hauenstein; Klaus Bengler (IEEE Access)
With the increasing integration of automated vehicles into urban traffic, understanding pedestrians’ interactions with automated vehicles is essential to ensure both safety and efficiency. As complex scenarios involving more than one pedestrian in real-world contexts remain underexplored, more clarification is needed on the relationship between additional pedestrians and automated vehicles’ communication. To address this, the present study investigates pedestrians’ crossing behavior in response to automated vehicles in a real-world setting, focusing on the influence of an additional pedestrian and the effectiveness of an external communication concept. A Wizard of Oz experiment was conducted in which a manually driven vehicle equipped with an external human-machine interface (eHMI) communicated its intent to pedestrians. Thirty-five participants took part in six scenarios that varied the automated vehicle’s communication mode (granting or claiming right of way) and the presence and behavior of an additional pedestrian (absent, compliant, or non-compliant with the automated vehicle’s intent). Results show that the presence and behavior of an additional pedestrian significantly influence crossing initiation time and decision-making, demonstrating the decisive role of social cues in automated vehicles-pedestrian interactions. Furthermore, participants interpreted the automated vehicle’s explicit communication reliably, supporting the effectiveness of the eHMI concept. The findings emphasize the necessity of robust automated vehicle communication strategies to facilitate safe pedestrian interactions in increasingly automated traffic environments.